2008
DOI: 10.2478/10004-1254-59-2008-1853
|View full text |Cite
|
Sign up to set email alerts
|

Lipid Peroxidation and Antioxidative Enzyme Activity in Erythrocytes of Workers Occupationally Exposed to Aluminium

Abstract: Current research indicates that lipid peroxidation could have a role in aluminium toxicity. The aim of this study was to asses lipid peroxidation and antioxidative enzyme activity in erythrocytes of workers occupationally exposed to aluminium. We investigated a group of 59 workers (Al group) exposed to aluminium fumes (contamination factor F=8.07 to 13.47, national maximal allowed concentration value is 2 mg m -3). The control group (C group) consisted of 75 subjects employed in lime production who had not bee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
12
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 29 publications
3
12
0
Order By: Relevance
“…These results are in accordance with our previous results on human erythrocytes (22) and with the data of Bulat et al (42).…”
Section: Discussionsupporting
confidence: 95%
See 1 more Smart Citation
“…These results are in accordance with our previous results on human erythrocytes (22) and with the data of Bulat et al (42).…”
Section: Discussionsupporting
confidence: 95%
“…Recently (22), we reported that human erythrocytes exposed to aluminum undergo lipid peroxidation as well as reduction in the activity of erythrocyte antioxidant enzymes (superoxide dismutase, catalase and glutathione peroxidase). A reduced activity of antioxidant enzymes following Al exposure has been reported also in workers occupationally exposed to aluminum (42). Free radical scavengers and chelators of aluminium lower ROS levels in brain cells.…”
Section: Discussionmentioning
confidence: 95%
“…However, according to the labels, the studied workers were exposed to toluene, xylene, ethylbenzene, butyl and ethyl acetate, acetone, methyl isobutyl ketone, titanium, aluminum, lead, cobalt, and chromium. It is already known that these compounds can induce DNA damages [15,[33][34][35] and an increase in oxidative stress chromosome rearrangement, and the NDI index is a biomarker of the proliferative status of the viable cell fraction [22]. An increase in NBUD frequency was observed in binucleated lymphocytes of the exposed group in Monday samples compared to Monday samples of the control group (Table 5), suggesting chromosomal damage and/or a DNA instability status in this group [22].…”
Section: Discussionmentioning
confidence: 86%
“…Measurement of (8-OHdG) is a highly sensitive assay for oxygen free radical damage to DNA (Canakci et al 2009;Valavanidis et al 2009). This biomarker has been used to estimate the DNA damage in humans after exposure to cancer-causing agents, such as heavy metals, and polycyclic aromatic hydrocarbons (Bulat et al 2008).…”
Section: Discussionmentioning
confidence: 99%